Ibadah Gereja Masa Pascapandemi Covid-19: Daring, Luring, atau Hibrid - Setya Hadi Nugroho; Niken D. Prananingtyas (Sekolah Tinggi Alkitab Jember, 2022)
After a long time, the Indonesian nation struggled against the COVID-19 pandemic, slowly the number of Covid-19 transmissions began to decline so that PPKM levels in various regions began to be lowered, and Many churches began to perform face-to-face worship (offline). This raises the question, of whether online worship will end soon, continue to go hand in hand with laryngeal worship, or even replace laryngeal worship. This research has been carried out using a qualitative method with a descriptive approach which is carried out through research literature from various kinds of references, such as books and journal articles related to this research, interviews with several sources, and of course theological research on worship based on the Testament Bible. Old and New Testament. From this research, the author concludes that in the future, offline and online ecclesiastical activities will continue to run together, support each other, strengthen and be able expand church services, especially in the context of building congregations and preaching the good news without having to debate the theological side and providing certainty, peace, both to the ministers of God and the church congregation. AbstrakSetelah sekian lama bangsa Indonesia berjuang melawan pandemi covid 19, perlahan-lahan jumlah penularan covid-19 mulai menurun, sehingga Level PPKM di berbagai daerah mulai diturunkan, Banyak gereja mulai melakukan ibadah tatap muka (luring). Hal ini menimbukan pertanyaan, apakah ibadah daring akan segera berakhir, tetap berjalan seiring dengan ibadah laring, atau bahkan menggantikan ibadah laring. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif yang dilakukan melalui literatur research dari berbagai macam referensi, seperti buku-buku dan jurnal yang berkaitan dengan penelitian ini, wawancara dengan beberapa nara-sumber serta tentu saja penelitian teologis ibadah berdasarkan Alkitab perjanjian lama dan Perjanjian baru. Dari penelitian ini, penulis menyimpukan bahwa kegiatan gerejawi secara luring dan daring akan tetap berjalan bersama, saling mendukung, memperkuat serta mampu memperluas pelayanan gereja, khususnya dalam rangka pembinaan jemaat dan pemberitaan kabar baik tanpa harus diperdebatkan lagi sisi teologisnya serta memberi kepastian, ketenangan, baik kepada para pelayan Tuhan maupun jemaat gereja.